Optimization of Sat Samapta Dialogic Patrols to Prevent the Criminal Act of Theft with Aggravating Factors in the Jurisdiction of Polres Pati - Yudhantara, Rafi Arya (Advances in Police Science Research Journal, 2024)
The police in carrying out their duties, one of which is to maintain security and public order from the dangers of crime, namely using preemptive or prevention. This is also carried out by the Samapta Polres Pati unit, namely by carrying out dialogic patrols to prevent criminal acts of theft by weighting in their jurisdiction. However, the implementation is considered to be still not optimal because according to the data, there are still many criminal acts of theft with weights that are troubling the Pati community. Therefore, this research focuses on the implementation of dialogic patrols to prevent criminal acts of theft by weighing in the jurisdiction of Polres Pati. In the research, the researcher uses a qualitative approach method with the type of field study research, which means that the researcher goes directly to the field. The researcher uses an analytical knife of organizational management theory and organizational resources and uses concepts that are following the focus of the problems formulated. The results obtained from this study are that the results of the dialogic patrols carried out by the Samapta Polres Pati Unit are still not optimal, marked by the efforts that have been implemented which are still not optimal, and the lack of management which is still not following the provisions causing currat crimes to still occur a lot in Starch Based on the results of the research that has been done, it can be concluded that the implementation of Sat Samapta Polres Pati dialogical patrols is considered not optimal because organizational resource factors and management factors are not yet effective and efficient so it is necessary to increase the implementation of Sat Samapta Polres Pati dialogical patrols to prevent criminal acts of theft by weighting.